Developing the modification of nickel cathodes for applying the ion-plasma coatings on the parts of aircraft engines - Yefanov, Vladimir; Ovchynnykov, Oleksandr; Dzhuhan, Oleksandr; Petrik, Ihor; Raspornia, Dmytro; Kapustian, Oleksii; Saprykin, Yehor (Eastern-European Journal of Enterprise Technologies, 2020)
This paper reports studying the effect of such highly active, surface-active modifying elements as Y, Hf, and La on the structure and properties of the Ni–Cr–Al system’s consumable cathodes, which are used to apply heat-resistant coatings onto the gas-turbine engines’ blades. Y, Hf, and La are introduced to form the nanoscale separation of phases that stabilize the alloy structure. In order to obtain cathodes of the required quality, a method of vacuum-arc autocrucible melting has been chosen. The selected technique makes it possible to use raw materials of different dispersity for the manufacture of ingots (in the form of powders or pig metal). The charge was prepared by shredding the materials mechanically, using various methods (cutting and crushing). It has been shown that the introduction of elements such as Y and La into the cathodes has a similar effect on structural formation processes. It has been established that when Hf is introduced, the structure of the resulting consumable cathodes is characterized by a greater degree of homogeneity. There is also a positive effect of Hf on the uniformity of the distribution of doping elements (Al, Cr) in the volume of the material compared to alloy samples modified by Y and La. It has been shown that the introduction of Hf has made it possible to achieve the higher quality indicators in comparison with Y and La. An analysis of coating structure has revealed that samples with Hf have a greater degree of homogeneity and fewer defects, which is especially important when applying coatings of greater thickness (over 40 µm). It has been established that the introduction of Hf makes it possible to apply coatings up to 90 µm thick by obtaining a less defective structure. It has been found that the Hf modification increases the adhesion between the substrate and coating, as well as makes it possible to achieve maximum even distribution of doping elements throughout the entire thickness of the coating applied